Performance modelling and optimization of disc angle and tractor speed for a disc ridger in loamy soil using RSM (International Journal of Agricultural Research, Innovation and Technology, 2025)
Ridging has been identified as a mechanized substitute for flat-land form and mounding in the cultivation of root and tuber crops. Manual ridging imposes high drudgery, consumes time and limits production scale. Therefore, mechanized ridging is necessary to improve efficiency, reduce cost and enable large-scale production. In this study, performance modelling and operational optimization of disc angle and tractor speed for a double-row disc ridger were established using CCRD in RSM. Quadratic models generated by RSM were used to predict optimum draught, wheel-slip and fuel consumption while maximizing cutting-depth and cutting-width. The results show that the ridger achieved optimum performance at 42.50 disc angle and 7.5 km/h tractor speed with a constant tilt angle of 25°. The regression model predicted optimal fuel consumption of 8.13 l/ha, 7.8 kN draught force, 2.8% wheel-slip, 29 cm depth and 277 cm width of cut, at the predicted disc angle and speed. The optimization analysis suggests that an increased disc angle and speed resulted in increased draught, fuel consumption, wheel-slip and cutting width and depth. To maximize operating efficiency, it is advised that ridging operations at the study site be conducted at the designated optimal speed and disc angle.Int. J. Agril. Res. Innov. Tech. 15(1): 62-69, June 2025